High doses of photons and carbon ions comparably increase vascular permeability in R3327-HI prostate tumors: a dynamic contrast-enhanced MRI study - Bendinger, Alina L.; Peschke, Peter; Peter, Jörg; Debus, Jürgen; Karger, Christian; Glowa, Christin (Radiation research, 2020)
Carbon- (12C-) ion radiotherapy exhibits enhanced biological effectiveness compared to photon radiotherapy, however, the contribution of its interaction with the vasculature remains debatable. The effect of high-dose 12C-ion and photon irradiation on vascular permeability in moderately differentiated rat prostate tumors was compared using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Syngeneic R3327-HI rat prostate tumors were irradiated with a single dose of either 18 or 37 Gy 12C ions, or 37 or 75 Gy 6-MV photons (sub-curative and curative dose levels, respectively). DCE-MRI was performed one day prior to and 3, 7, 14 and 21 days postirradiation. Voxel-based tumor concentration-time curves were clustered based on their curve shape and treatment response was assessed as the longitudinal changes in the relative abundance per cluster. Radiation-induced vascular damage and increased permeability occurred at day 7 postirradiation for all treatment groups except for the 75 Gy photon-irradiated group, where the onset of vascular damage was delayed until day 14. No differences between irradiation modalities were found. Therefore, early vascular damage cannot explain the higher effectiveness of 12C ions relative to photons in terms of local tumor control for this moderately differentiated prostate tumor and the applied single high doses.
Gesehen am 18.01.2021